RUPTURES IN CLIMATE DISCOURSE: DIGITAL PUBLICS, POLARISATION, AND ENVIRONMENTAL CONFLICT IN AUSTRALIA AND BRAZIL - Choucair, Tariq; Recuero, Raquel; Bruns, Axel; Lubicz-Zaorski, Carly; Antonelli, Thales; Maia, Rousiley; Esau, Katharina; Vodden, Laura; Dehghan, Ehsan; Vilkins, Samantha; Santini, R. Marie; Gomes Salles, Debora; et al. (AoIR Selected Papers of Internet Research, 2026)
Australia and Brazil are on the frontlines of climate crises. Both have experienced significant warming, including intense heatwaves. Both have experienced changes in rainfall patterns, with increases in some regions and decreases in others, affecting biodiversity, agriculture, and infrastructure. Floods and largely destructive bushfires have been major events both countries dealt with in the last decade. The frequency and intensity of such extreme events like bushfires and floods are expected to increase, further increasing the impact to ecosystems and cities. Beyond suffering similar consequences of climate change, both economies rely on extractive industries (mining, agribusiness, and fossil fuels). Brazil is the sixth largest global greenhouse gas emitter, while Australia is one of the largest per capita emitters of greenhouse gases, largely due to its reliance on coal for energy and as an export commodity.In addition to the consequences and causes of climate change, climate activism and advocacy in both countries are highly driven by indigenous and other vulnerable communities, who are also the ones suffering the most severe consequences of ecological destruction. This panel brings together papers that investigate how climate debates unfold in these two nations, focusing on digital public spheres, political polarisation, and discursive struggles over climate action. By examining data from Facebook, WhatsApp, Telegram, news media, and parliamentary debates, these papers reveal how climate discussions are shaped by ideological divides, strategic narratives, platforms affordances, and moments of crisis.The first key theme in our panel is how climate discourse is shaped by the experience of extreme weather events. Paper 1 analyzes online climate discussions in Brazil, investigating if extreme weather events trigger spikes in public engagement, and if political and media framing influence whether these discussions translate into sustained climate awareness. Similarly, Paper 2 tracks shift in Australian climate discourses on Facebook, paying attention if events such as the catastrophic 2019–2020 bushfires intensify debates on climate action.A second key theme across our panel is the problematization of digital platforms’ mediation of climate polarisation. Paper 1 and Paper 2 analyse multiple years of Facebook discourses including different types of users (e.g., news media, activists), while Paper 3 analyse far-right climate discussions in Brazilian WhatsApp and Telegram groups. Paper 4 brings another dimension by investigating Australian online news media. We then cover a wide range of online arenas, allowing a granular view on the role of different spaces for the overall climate discussions.A third key theme is the formation of discursive alliances or coalitions (groups of actors who align around shared climate narratives) and the circulation of arguments and claims. Paper 2 employs a novel practice mapping method to identify distinct climate discourse clusters in Australia. Paper 4 extends this analysis to the political arena, mapping the alliances that form around climate issues in news reporting and parliamentary debates. Similarly, Paper 5 examines how parliamentary discourse in Brazil intersects with climate debates, particularly in discussions on land conflicts and territorial rights. It investigates weather climate narratives are weaponized to delegitimise land rights movements, aligning agribusiness interests with climate delay rhetoric.A fourth key theme is the role of far-right actors in shaping climate discourse. Paper 3 provides an in-depth look at how Brazilian far-right groups on WhatsApp and Telegram use climate issues to reinforce political polarisation. It identifies recurring themes, including attacks on environmental NGOs, conspiratorial claims that climate change is a globalist hoax, and narratives that portray agribusiness as under siege by environmental regulations. Paper 4 finds parallel trends in Australia, where climate delay discourses have evolved from outright denial to more sophisticated tactics. Paper 5 adds another layer by examining how parliamentary actors in Brazil use climate narratives to delegitimise land struggles, further embedding climate discourse within broader ideological battles.Finally, our panel considers the intersection of media narratives, policy debates, and public engagement. Paper 1 and Paper 2 highlight how news coverage and online engagement influence climate discussions, while Paper 4 systematically maps how claims discursively connect media reporting with public submissions to parliamentary inquiries. Paper 5 provides a historical perspective by tracing three decades of Brazilian parliamentary debates on land and climate, revealing how formal political discourse evolves in response to shifting environmental and economic pressures.